The role of contextualisation in enhancing non-communicable disease programmes and policy implementation to achieve health for all - Hueiming Liu; Mark D. Huffman; Kathy Trieu (BMC, 2020)
Abstract The September 2019 United Nations' High-Level Meeting renewed political commitments to invest in universal health coverage by strengthening health systems, programmes and policies to achieve 'health for all'. This Political Declaration is relevant to addressing the increasing global burden of non-communicable diseases, but how can evidence-based programmes and policies be meaningfully implemented and integrated into local contexts? In this Commentary, we describe how the process of contextualisation and associated tools, such as ecological frameworks, implementation research frameworks, health system indicators, effective system strengthening strategies and evidence mapping databases with priority-setting, can enhance the implementation and integration of non-communicable disease prevention and control policies and programmes. Examples across health platforms include (1) population approaches to reducing excess sodium intake, (2) fixed-dose combination therapy for cardiovascular disease prevention and control, and (3) health systems strengthening for improving the quality and safety of cardiovascular care. Contextualisation is needed to transfer evidence into locally relevant and impactful policies and programmes. The systematic and comprehensive use of contextualisation tools leverages key implementation research principles to achieve 'health for all'.